Comparative transcriptome analysis of anthocyanin synthesis in black and pink peanut. (1st February 2020) - Xia, Han; Zhu, Lin; Zhao, Chuanzhi; Li, Ke; Shang, Caili; Hou, Lei; Wang, Mingxiao; Shi, Jing; Fan, Shoujin; Wang, Xingjun
ABSTRACT: In recent years, black testa peanut ( Arachis hypogaea L.) has been favored because of its nutritional value and health function. To explore the genetic basis of peanut testa color, high-throughput sequencing technology was used to sequence the transcriptome of black testa peanut 'ZH9ʹ and pink testa peanut 'ZH8.ʹ Over 18 million high-quality reads were assembled into 49, 404–52, 578 genes for these two cultivars using a combined assembly strategy. Totally, 4, 122 differentially expressed genes (DEGs) were identified between ZH8 and ZH9, among which 1317 (32%) were up-regulated and 2805 (68%) were down-regulated. KEGG analysis showed that the pathways of anthocyanin biosynthesis, isoflavonoid biosynthesis, flavone and flavonol biosynthesis, and phenylpropanoid biosynthesis were in the top 20 differentially expressed genes enriched pathways. Further analysis showed that the formation of the black color of ZH9 testa was mainly due to the reduction of lignin biosynthesis and isoflavonoid biosynthesis, and as a result, more substrate flow to anthocyanin biosynthesis. The up-regulation of all genes associated with DFR, a key enzyme determining flavonoid synthesis or anthocyanin synthesis in the flavonoid metabolic pathway, is also a strategy for increasing dihydroflavonol, a substrate for anthocyanin and flavonol biosynthesis. In addition, we identified three up-regulated R2R3MYB transcription factors associated with anthocyanin biosynthesis in ZH9. Finally, we verified the expressions of 15 genes that encode key enzymes and transcription factors using quantitative real-time PCR (qRT-PCR).